Surviving cell-sharing: Resistance, cooperation and collaboration. (April 2023) - Muirhead, Aimee; Butler, Michelle; Davidson, Gavin
For decades, researchers have sought to understand the impact of imprisonment; yet we have a limited understanding of the lived experience of cell-sharing. To address this gap in knowledge, this paper draws on 37 semi-structured interviews with imprisoned adult men in Northern Ireland. While demonstrating that, for most, cell-sharing was a negative experience, imbued with discomfort, unease and distress, a new conceptual framework is presented that seeks to understand the tactics people use to manage cell-sharing, influences on their choice of tactics and the potential repercussions of these tactics. Potential implications for policy and practice are also discussed.